Predictive value of serum lipoprotein-associated phospholipase A2 for coronary atherosclerotic heart disease in elderly patients with hypertension - Zhang Mimi; Fan Rong (Guoji laonian yixue zazhi)
[Objective] To investigate the predictive value of lipoprotein-associated phospholipase A2 (Lp-PLA2) on coronary atherosclerotic heart disease(abbreviated as coronary heart disease) in elderly patients with hypertension. [Methods] A total of 68 coronary heart disease patients with hypertension admitted to the East Campus of Xi'an Jiaotong University First Affiliated Hospital from April 2020 to May 2023 were selected as the coronary heart disease group, while another 91 patients with pure hypertension were selected as the non-coronary heart disease group. Clinical data and laboratory indicators of the patients were recorded. All patients underwent coronary angiography, and patients in the coronary heart disease group were divided into the mild-to-moderate group (35 cases) and the severe group (33 cases) based on the Gensini score. Logistic regression model analysis was used to examine the relationship between various variables and the occurrence and severity of coronary heart disease, while ROC curves were employed to analyze the predictive efficiency of these variables in terms of the occurrence and severity of coronary heart disease. [Results] The proportion of patients with hypertension duration ≥ 5 years, low-density lipoprotein cholesterol, angiotensin Ⅱ, apolipoprotein B, and Lp-PLA2 were higher in the coronary heart disease group compared to the non-coronary heart disease group（P<0.05）, while apolipoprotein A1 was lower (P<0.05). Logistic regression analysis revealed that hypertension duration ≥5 years and Lp-PLA2 were independent risk factors for predicting hypertension with coronary heart disease (P<0.05). The AUC value of Lp-PLA2 for predicting hypertension with coronary heart disease was 0.740 (95%CI: 0.672-0.809, P<0.001).In the severe group, the proportion of patients with disease duration ≥ 5 years, the proportion of smokers, angiotensin Ⅱ, and Lp-PLA2 were higher than those in the mild-to-moderate group (P<0.05). logistic regression analysis showed that Lp-PLA2 was an independent risk factor for predicting hypertension with severe coronary heart disease (P<0.05). The AUC value of Lp-PLA2 for predicting hypertension with severe coronary heart disease was 0.821 (95%CI: 0.719-0.923，P<0.001). [Conclusion] The serum Lp-PLA2 level in elderly patients with hypertension has a certain predictive value for predicting the occurrence and severity of coronary heart disease.